Overexpression of wild-type ANXA7 tumor suppressor gene alters cancer-related micrornas in human prostate cancer cells / Yap Lim Hui - Yap, Lim Hui (2013)
MicroRNAs (miRNAs) are endogenous 18-25nt RNAs that regulate genes at the protein translation level. They can act as tumor suppressors or oncogene and are often dysregulated in various cancers. ANXA7 is a tumor suppressor gene that encodes for a Ca2+-dependent membrane-binding protein and its expression was found to be reduced or lost in advanced androgen-independent prostate cancers. This research aims to identify miRNAs that are regulated by the ANXA7 tumor suppressor gene and the putative pathways involved in prostate cancer. The overexpression of wild-type ANXA7 was achieved by using a mammalian expression vector harboring the gene. From our miRNA microarray expression, a total of 16 miRNAs were found to be significantly differentially expressed in response to increased ANXA7. These include hsa-miR-874, hsa-miR-1284, hsa-miR-543 and hsa-miR-409-5p. All of these miRNAs have predicted targets that are involved in calcium signaling. In conclusion, the altered miRNA expression induced upon increased expression of ANXA7 suggests that miRNAs and the calcium signaling pathways are regulated by ANXA7 and could be manipulated for therapeutic purposes.